Azerbaijan Republic : Staff Report for the 2003 Article IV Consultation, Second Review Under the Poverty Reduction and Growth Facility, and Requests for Waivers of Performance Criteria, Extension of Arrangement and Rephasing of Purchases. (IMF Staff Country Reports; Country Report ;, 2003)
This paper evaluates Azerbaijan's 2003 Article IV Consultation, Second Review Under the Poverty Reduction and Growth Facility (PRGF), and Requests for Waivers of Performance Criteria, Extension of Arrangement and Rephasing of Purchases. Performance relative to the quantitative targets under the program was strong, as all quantitative performance criteria and most indicative targets were met. Implementation of the structural reforms under the program was slower than planned, delaying completion of the second review. The authorities are requesting several waivers related to delays in structural reforms.